Survival of Air Asia in low cost airline industry / Mohd Khairi Asyraf Roslan and Shasha Nurshafika Hamsah - Roslan, Mohd Khairi Asyraf; Hamsah, Shasha Nurshafika (Faculty of Business and Management, 2014)
Air Asia was established on 12th December 2001 by a determine guy name Tony Fernandes. He begins to involve airline business by creatinga new company named Tune Air with three of his partners. During the 3rd quarter of 2001, his company willing to purchase Air Asia company for the unbelievable price of RM 1 but he must take over 50% of Air Asia’s net liabilities around the RM 40m worth of debts together. The company grows slowly from time to time to be one of the successful low cost airlines in the industry. By using a simple yet strong slogan “Now Everyone Can Fly”, it makes their brands positioned in most of the customer’s mind as the cheap and affordable airline fare. Nowadays, Air Asia has over 20 routes around the globe in its network and it will continue to increase to conquer the low cost airline industry through its innovative solutions, efficient processes and appropriate strategy to business. The biggest achievements they earn are being awarded as the world’s best airline company by Skytraxx for four consecutive years which is from 2009 until 2012. This achievement shows that Air Asia must maintain their business and find the new strategy to attract more people to use their service.